Phytochemical analysis and antimicrobial activities of methanolic extracts of leaf, stem and root from different varieties of Labisa pumila Benth. - Karimi, Ehsan; Jaafar, Hawa; Ahmad, Sahida (MDPI, 2011)
A local herb, Kacip Fatimah, is famous amongst Malay women for its uses in parturition; however, its phytochemical contents have not been fully documented. Therefore, a study was performed to evaluate the phenolics, flavonoids, and total saponin contents, and antibacterial and antifungal properties of the leaf, stem and root of three varieties of Labisia pumila Benth. Total saponins were found to be higher in the leaves of all three varieties, compared to the roots and stems. Leaves of var. pumila exhibited significantly higher total saponin content than var. alata and lanceolata, with values of 56.4, 43.6 and 42.3 mg diosgenin equivalent/g dry weight, respectively. HPLC analyses of phenolics and flavonoids in all three varieties revealed the presence of gallic acid, caffeic acid, rutin, and myricetin in all plant parts. Higher levels of flavonoids (rutin, quercitin, kaempferol) were observed in var. pumila compared with alata and lanceolata, whereas higher accumulation of phenolics (gallic acid, pyrogallol) was recorded in var. alata, followed by pumila and lanceolata. Antibacterial activities of leaf, stem and root extracts of all varieties determined against both Gram positive (Micrococcus luteus, Bacillus subtilis B145, Bacillus cereus B43, Staphylococcus aureus S1431) and Gram negative (Enterobacter aerogenes, Klebsiella pneumonia K36, Escherichia coli E256, Pseudomonas aeruginosa PI96) pathogens showed that crude methanolic extracts are active against these bacteria at low concentrations, albeit with lower antibacterial activity compared to kanamycin used as the control. Antifungal activity of methanolic extracts of all plant parts against Fusarium sp., Candida sp. and Mucor using the agar diffusion disc exhibited moderate to appreciable antifungal activities compared to streptomycin used as positive control.